Paretian Distributions and Income Maximization - Mandelbrot, Benoit (Quarterly Journal of Economics, 1962)
I. The empirical distribution of income. Scope of the weak law of Pareto, 58. — II. Scope of the present paper, 59. — III. Linear factor analysis of the rental price of an undissoluble bundle of abilities, 60. — IV. The regions of acceptance of the different offers, 62. — V. The assumption that the factors themselves are Paretian, 64. — VI. The conclusion that the offers accepted from different occupations will be Paretian, with an alpha exponent integral multiple of that of the factors, 68. — VII. The evaluation of the asymptotic Paretian weight of an occupation, 70. — VIII. The behavior of the densities before the Paretian asymptotic range is reached; the log-normal approximation, 72. — IX. Elasticities of the distribution of people among various occupations, 77. — X. A concluding remark concerning regional differences in the value of alpha, 79. — Appendices, 79.